2020
DOI: 10.3892/mmr.2020.11300
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed lncRNAs, miRNAs and mRNAs with associated ceRNA networks in a mouse model of myocardial ischemia/reperfusion injury

Abstract: Non-coding RNAs, including long non-coding RNAs (lncRNAs) and microRNAs (miRNAs/miRs), have significant regulatory effects on a number of biological processes in myocardial ischemia/reperfusion (I/R) injury, including cell differentiation, proliferation and apoptosis. In the present study, the expression levels of lncRNAs, miRNAs and mRNAs were evaluated in a mouse model of myocardial I/R injury. The potential functions of these differentially expressed genes were then analyzed via Gene Ontology and pathway an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Long noncoding RNA can act as a molecular sponge for miRNA to release the downstream target mRNA (Zhou et al 2018;Zhang et al 2020;Zou et al 2020). We anticipated that SOX2-OT regulated H9c2 cell injury by this pattern.…”
Section: Sox2-ot Worked As a Sponge For Mir-215-5pmentioning
confidence: 99%
“…Long noncoding RNA can act as a molecular sponge for miRNA to release the downstream target mRNA (Zhou et al 2018;Zhang et al 2020;Zou et al 2020). We anticipated that SOX2-OT regulated H9c2 cell injury by this pattern.…”
Section: Sox2-ot Worked As a Sponge For Mir-215-5pmentioning
confidence: 99%
“…Regulating lncRNAs expression has neuroprotective effects in AIS cells and animal models. In addition, most of these lncRNAs regulate the expression of their downstream mRNAs by sponging their target miRNAs, which regulates oxidative stress ( Zhang et al, 2020c ). These recent studies provide a new mechanism for lncRNAs to participate in AIS pathogenesis and suggest potential novel therapeutic strategies for AIS.…”
Section: Lncrnas Mediating Oxidative Stress In Central Nervous System...mentioning
confidence: 99%
“…Hence, the inhibitory effect of miRNA on mRNA might be canceled when miRNAs is combined with MRE on lncRNA. Recently, accumulating studies have demonstrated that the ceRNA network has become increasingly important in the occurrence and progression of diverse diseases, including cancers, Parkinson’s disease, myocardial ischemia/reperfusion injury, and cerebral infarction ( Zou et al, 2019 ; Qi et al, 2020 ; Zhang R. et al, 2020 ; Zhang X. et al, 2020 ). Nonetheless, few studies of ceRNA network in SCII have been reported ( Liu et al, 2018 ; Qiao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%